Pemberdayaan Masyarakat sebagai Upaya Meningkatkan Ketahanan Pangan Keluarga dan Mengurangi Stunting di Nagari Koto VIII Pelangai Kabupaten Pesisir Selatan - Afriza Ayu, Gabriella; Yusran, Rahmadani (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This research focuses on community empowerment in Nagari Koto VIII Pelangai, Pesisir Selatan Regency, in improving family food security to prevent stunting. Data was collected using interviews and documentation, using a descriptive qualitative approach. Data analysis was carried out using reduction, presentation, and conclusion drawing. This study refers to Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction, which emphasizes community-based interventions. The results show that community empowerment in family food security has not achieved policy objectives. The main obstacles found are limited experts, the tendency of people to choose instant solutions, lack of budget support, and low awareness in caring for food seedlings. Nevertheless, community empowerment remains an important strategy for improving food security and reducing stunting. There is a need to increase technical training, strengthen budget support, and build community awareness to be more active in this program.